2021 PACES expert consensus statement on the indications and management of cardiovascular implantable electronic devices in pediatric patients: Executive summary - Writing Committee Members; Silka, Michael J; Shah, Maully J; Avari Silva, Jennifer N; Balaji, Seshadri; Beach, Cheyenne M; Benjamin, Monica N; Berul, Charles I; Cannon, Bryan; Cecchin, Frank; Cohen, Mitchell I; Dalal, Aarti S; et al. (Indian pacing and electrophysiology journal, 2021)
Guidelines for the implantation of cardiac implantable electronic devices (CIEDs) have evolved since publication of the initial ACC/AHA pacemaker guidelines in 1984 [1]. CIEDs have evolved to include novel forms of cardiac pacing, the development of implantable cardioverter defibrillators (ICDs) and the introduction of devices for long term monitoring of heart rhythm and other physiologic parameters. In view of the increasing complexity of both devices and patients, practice guidelines, by necessity, have become increasingly specific. In 2018, the ACC/AHA/HRS published Guidelines on the Evaluation and Management of Patients with Bradycardia and Cardiac Conduction Delay [2], which were specific recommendations for patients >18 years of age. This age-specific threshold was established in view of the differing indications for CIEDs in young patients as well as size-specific technology factors. Therefore, the following document was developed to update and further delineate indications for the use and management of CIEDs in pediatric patients, defined as ≤21 years of age, with recognition that there is often overlap in the care of patents between 18 and 21 years of age. This document is an abbreviated expert consensus statement (ECS) intended to focus primarily on the indications for CIEDs in the setting of specific disease/diagnostic categories. This document will also provide guidance regarding the management of lead systems and follow-up evaluation for pediatric patients with CIEDs. The recommendations are presented in an abbreviated modular format, with each section including the complete table of recommendations along with a brief synopsis of supportive text and select references to provide some context for the recommendations. This document is not intended to provide an exhaustive discussion of the basis for each of the recommendations, which are further addressed in the comprehensive PACES-CIED document [3], with further data easily accessible in electronic searches or textbooks.
Keywords: Cardiomyopathy; Bradycardia; Implantable cardioverter defibrillator; Catecholaminergic polymorphic ventricular tachycardia; Epicardial lead; Insertable cardiac monitor; Lead extraction; Transvenous; ECG; Ventricular tachycardia; Lead removal; PACES; Postoperative; Sick sinus syndrome; Echocardiography; Antiarrhythmic drug therapy; Shared decision-making; Low- and middle-income countries; Heart failure; Ventricular fibrillation; Cardiac transplantation; Sports and physical activity; MR imaging; Pediatrics; Congenital heart disease; Sudden cardiac arrest; Antitachycardia pacing; Asystole; Sudden cardiac death; Long QT syndrome; Syncope; Cardiovascular implantable electronic devices; Pacemaker; Remote monitoring; Neuromuscular disease; Heart block; Ambulatory ECG monitoring; Endocardial lead; Brugada syndrome; Cardiac channelopathies; Hypertrophic cardiomyopathy; Expert consensus statement; Genetic arrhythmias; Arrhythmogenic cardiomyopathy; Children; Atrioventricular block; Coronary artery compression